Analysis of Factors Influencing Purchase Decisions at Indomaret Retail Stores - Nia Anggraini; Erfa Okta Lussianda; Dodi Agusra; Muhammad Adrian; Awliya Afwa (Asean International Journal of Business, 2023)
This study aims to identify and analyze the factors that influence purchasing decisions at Indomaret in Pekanbaru. The object of research is customers who shop at Indomaret in Pekanbaru City. The technique of determining the sample by nonprobability sampling, using the incidental sampling method. The data analysis technique used Structural equation modeling using the Smart PLS version 3 application. The findings from this study note that price and product completeness have a positive effect on purchasing decisions at Indomaret. While location has a positive and significant effect onbuying decision. Based on the determination test it was concluded that product completeness, location and price simultaneously influence purchasing decisions at Indomaret in Pekanbaru. For future researchers, it is hoped that the results of this study can become a reference for research with similar titles and add other variables to be examined in depth. Â